2023
DOI: 10.3390/foods12163089
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Enzymatic Performance of β-Mannanase Immobilized on Calcium Alginate Beads for the Generation of Mannan Oligosaccharides

Xinggang Chen,
Zhuang Tian,
Hongbo Zhou
et al.

Abstract: Mannan oligosaccharides (MOSs) are excellent prebiotics that are usually obtained via the enzymatic hydrolysis of mannan. In order to reduce the cost of preparing MOSs, immobilized enzymes that demonstrate good performance, require simple preparation, and are safe, inexpensive, and reusable must be developed urgently. In this study, β-mannanase was immobilized on calcium alginate (CaAlg). Under the optimal conditions of 320 U enzyme addition, 1.6% sodium alginate, 2% CaCl2, and 1 h of immobilization time, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…This trend of shifting the optimal pH toward less acidic conditions was also noted Dhiman et al (2020) for β-mannanase supported on cyclodextrin grafted with sodium ginate [22], and by Chen et al (2023), who also immobilized β-mannanase on sodium ginate [33]. This alteration in the optimal pH is typically associated with variations in ionic environment surrounding the enzyme's active sites.…”
Section: Effect Of Phsupporting
confidence: 69%
See 2 more Smart Citations
“…This trend of shifting the optimal pH toward less acidic conditions was also noted Dhiman et al (2020) for β-mannanase supported on cyclodextrin grafted with sodium ginate [22], and by Chen et al (2023), who also immobilized β-mannanase on sodium ginate [33]. This alteration in the optimal pH is typically associated with variations in ionic environment surrounding the enzyme's active sites.…”
Section: Effect Of Phsupporting
confidence: 69%
“…Other authors who have immobilized β-mannanase have also conducted stability tests, typically for 10 cycles. However, in their studies, they observed a more pronounced decrease in activity compared to what was reported in this work [9,33]. This result demonstrates the effectiveness of the immobilization methodology and the type of support used to retain enzymatic activity.…”
Section: Operational Stabilitysupporting
confidence: 44%
See 1 more Smart Citation